Natural Killer Cells in Systemic Autoinflammatory Diseases: A Focus on Systemic Juvenile Idiopathic Arthritis and Macrophage Activation Syndrome - Vandenhaute, Jessica; Wouters, Carine H.; Matthys, Patrick (Frontiers in Immunology, 2020)
Natural killer (NK) cells are innate immune lymphocytes with potent cytolytic and immune-regulatory activities. NK cells are well known for their ability to kill infected and malignant cells in a fast and non-specific way without prior sensitization. For this purpose, NK cells are equipped with a set of cytotoxic molecules such as perforine and apoptosis-inducing proteins. NK cells also have the capacity to produce large amounts of cytokines and chemokines that synergize with their cytotoxic function and that ensure interaction with other immune cells. A less known feature of NK cells is their capacity to kill non-infected autologous cells, such as immature dendritic cells and activated T cells and monocytes. Via the release of large amounts of TNF-α and IFN-γ, NK cells may contribute to disease pathology. Conversely, they may exert a regulatory role through secretion of immuno-regulatory cytokines such as GM-CSF, IL-13 and IL-10. Thus, NK cells may be important target and effector cells in the pathogenesis of autoinflammatory diseases, in particular in those disorders associated with a cytokine storm or in conditions where immune cells are highly activated. Key examples of such diseases are systemic juvenile idiopathic arthritis (sJIA) and its well-associated complication, macrophage activation syndrome (MAS). sJIA is a chronic childhood immune disorder of unknown etiology, characterized by arthritis and systemic inflammation, including a daily spiking fever and evanescent rash. MAS is a potentially fatal complication of autoimmune and autoinflammatory diseases, and most prevalently associated with sJIA. MAS is considered as a subtype of hemophagocytic lymphohistiocytosis (HLH), a systemic hyperinflammatory disorder characterized by defective cytotoxic pathways of cytotoxic T and NK cells. In this review, we describe the established NK cells in sJIA and MAS features of NK cells and provide the results of a literature survey on the reported NK cell abnormalities in monogenic and multifactorial autoinflammatory disorders. Finally, we discuss the role of NK cells in the pathogenesis of sJIA and MAS.